A multi-parent faba bean (Vicia faba L.) population for future genomic studies. Issue 5 (2nd October 2018) - Khazaei, Hamid; Stoddard, Frederick L.; Purves, Randy W.; Vandenberg, Albert
Abstract: Faba bean ( Vicia faba L.) is a valuable grain legume and a staple protein crop in many countries. Its large and complex genome requires novel approaches for its genetic dissection. Here we introduce a multi-parent population developed from four founders (ILB 938/2, Disco/2, IG 114476 and IG 132238). The selection of parental lines was based on geographic (Colombia, France, Bangladesh and China), genetic and phenotypic diversity. The parental lines were inbred and then genotyped using 875 single nucleotide polymorphism (SNP) markers. Based on molecular data, the parents had high homozygosity and high genetic distance among them. The population segregates for several important traits such as seed morphology, seed chemistry, phenology, plant architecture, drought response, yield and its components, and resistance to Botrytis fabae. The population was checked for unbiased segregation in each generation by observing simply inherited Mendelian traits such as stipule spot pigmentation (SSP) and flower colour at different generations. All 1200 four-way cross F1 plants had pigmented flowers and stipule spots. The segregation ratios for white flower colour (single gene, zt2 ) fit 7:1, 13:3 and 25:7 at F2, F3 and F4 generations, respectively, and the segregation ratio of SSP (two recessive unlinked genes, ssp1 and ssp2 ) fit 49:15 and 169:87 at the F2 and F3 generations, respectively, demonstrating unbiased generation advance. We will subject the F5 generation of this population to a high-throughput SNP array and make it available for further phenotyping and genotyping.